2014
DOI: 10.1186/s12983-014-0063-z
|View full text |Cite
|
Sign up to set email alerts
|

The cerato-mandibular ligament: a key functional trait for grazing in damselfishes (Pomacentridae)

Abstract: Introduction: The success of a taxonomic group can be promoted by a key character that allows the group to interact with its environment in a different way and to potentially occupy new niches. The Pomacentridae possess a synapomorphic trait, the cerato-mandibular (c-md) ligament, which joins the hyoid bar to the inner part of the lower jaw. It has previously been shown that this ligament is a key trait in communication in damselfishes because it enables them to slam the oral jaws shut causing teeth collision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 74 publications
(84 reference statements)
1
23
0
Order By: Relevance
“…Exclusively morphological studies have shown that damselfish trophic evolution can be characterized as repeated adaptation to planktivory, omnivory and herbivory Frédérich et al, 2016Frédérich et al, , 2013Olivier et al, 2014) and this description is further supported by our combined analyses of both morphological and kinematic data (Table 4). Heavy feeding on detritus has evolved at least three times in herbivorous damselfishes (Stegastes nigricans, Hemiglyphidodon plagiometopon and Dischistodus perspicilliatus; Wilson and Bellwood, 1997) and the four-peak OU model, which included detritivory, had a fit to our data that was nearly as good as OU 3.2 (Table 4).…”
Section: Trade-offs In Damselfish Feedingsupporting
confidence: 80%
“…Exclusively morphological studies have shown that damselfish trophic evolution can be characterized as repeated adaptation to planktivory, omnivory and herbivory Frédérich et al, 2016Frédérich et al, , 2013Olivier et al, 2014) and this description is further supported by our combined analyses of both morphological and kinematic data (Table 4). Heavy feeding on detritus has evolved at least three times in herbivorous damselfishes (Stegastes nigricans, Hemiglyphidodon plagiometopon and Dischistodus perspicilliatus; Wilson and Bellwood, 1997) and the four-peak OU model, which included detritivory, had a fit to our data that was nearly as good as OU 3.2 (Table 4).…”
Section: Trade-offs In Damselfish Feedingsupporting
confidence: 80%
“…Beside sound production, the function of the ceratomandibular ligament, a morphological novelty, provides a diversification in the feeding mechanism (Frédérich, Olivier, Litsios, Alfaro, & Parmentier, ; Olivier, Frédérich, Herrel, & Parmentier, ). In the filamentous algae grazer Cortez damselfish ( Stegastes rectifraenum Pomacentridae), the slam occurs during feeding and simultaneously produces sounds (Olivier et al ., ). The same morpho‐functional process occurs in the anemonefish A. clarkii .…”
Section: The Concept Of Exaptationmentioning
confidence: 97%
“…Rapid mouth closure is forced by a synapomorphic ceratomandibular ligament (Stiassny, ) joining the lateral side of the hyoid bar to the medial side of the mandible. Experiments on anesthetized specimens show the jaw slam is caused by the stretched ligament and does not require adductor muscle contraction (Olivier, Frédérich, Spanopoulos‐Zarco, Balart, & Parmentier, ). Further, cutting the ceratomandibular ligaments prevents both feeding and sound production.…”
Section: The Concept Of Exaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they independently evolved jaw protrusion ability, thus providing one case of this convergent feature, allowing the analyses of how different ontogenetic trajectories reach similar solutions . In addition, they possess peculiar anatomical traits to graze filamentous algae and to produce sounds during numerous social interactions . The clownfish also provide a unique model for the evolution of pigment pattern that allows the study of how ecology and development can permit and constrain the diversification of complex patterns .…”
Section: Introductionmentioning
confidence: 99%